Classification and Outcome Measures for Psoriatic Arthritis - Leung, Ying Ying; Ogdie, Alexis; Orbai, Ana-Maria; Tillett, William; Coates, Laura C.; Strand, Vibeke; Mease, Philip; Gladman, Dafna D. (Frontiers in Medicine, 2018)
Psoriatic arthritis (PsA) is an inflammatory arthritis with multiple manifestations: peripheral/ axial arthritis, enthesitis, dactylitis, psoriasis and nail involvement. From having an agreed upon classification criteria in 2006, the assessment of PsA has advanced from uncertainties to development and validation of numerous specific outcome measures. The Group for Research and Assessment of Psoriasis and Psoriatic arthritis (GRAPPA) has spearheaded the development of a core domain set and is now working on a core outcome measurement set to standardize outcome measures for PsA, that will provide guidance for use of instruments in randomized controlled trials (RCTs) and longitudinal observational studies (LOS). This article summarizes and updates these work processes to improve assessment of this multisystem complex rheumatologic disease.